2004
DOI: 10.1002/jtra.10055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin treatment on liver and thymus zinc levels in young and middle‐aged rats

Abstract: Melatonin (MEL) is the main neurohormone of the pineal gland. Zinc (Zn) is an essential trace element that is required as a catalytic component for more than 200 enzymes. Both MEL and Zn are considered beneficial for anti-immunosenescence. Recent findings have shown that MEL can modulate Zn turnover. The aim of this study was to investigate the effect of MEL treatment on the tissue Zn levels in young (4 months) and middle-aged (14 months) rats. Male wistar rats received during 3 weeks subcutaneous injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Melatonin is reported to regulate zinc turnover. Öztürk et al showed that liver zinc levels were reduced by age and melatonin recovered age-related decrement in zinc levels of the thymus tissue in elderly rats [87]. Moreover, in another study, melatonin treatment has been shown to increase zinc level in the small intestines of young rats during night time, while it increased zinc levels in salivary glands during day and night time via the zinc absorption from small intestines [88].…”
Section: Melatonin and The Immune Systemmentioning
confidence: 96%
See 1 more Smart Citation
“…Melatonin is reported to regulate zinc turnover. Öztürk et al showed that liver zinc levels were reduced by age and melatonin recovered age-related decrement in zinc levels of the thymus tissue in elderly rats [87]. Moreover, in another study, melatonin treatment has been shown to increase zinc level in the small intestines of young rats during night time, while it increased zinc levels in salivary glands during day and night time via the zinc absorption from small intestines [88].…”
Section: Melatonin and The Immune Systemmentioning
confidence: 96%
“…Notably, the main target of melatonin is the thymus which is the central organ of the immune system [85]. The effects of melatonin on thymus endocrine activity and immune functions are partly dependent on its relation to zinc, which is an essential component of more than 200 enzymes [84,86,87]. Zinc contributes to the age related changes in the immune system, and the zinc pool is altered with aging.…”
Section: Melatonin and The Immune Systemmentioning
confidence: 99%
“…It was also shown that tissue Zn levels were changed after pinealectomy in rats (Mocchegiani et al, 1994a;Cunnane, Horrobin, Manku, & Oka, 1979). Our previous studies have shown that MEL treatment changed Zn levels of tissues and serum in rats (Ö ztü rk, Coşkun, Erbaş, & Altunkaynak, 2002;Ö ztü rk, Akbulut, Afrasyap, & Sevinç, 2004).…”
mentioning
confidence: 90%